A distância geográfica aumenta a dissimilaridade de interações entre formigas e insetos trofobiontes através da substituição das espécies envolvidas - Matheus de Morais Belchior Couto (2021)
The different types of mutualistic interactions, such as pollination, seed dispersal, and ant-plant mutualisms, have been examined from the perspective of interaction networks. Among the aspects addressed, the "β-diversity of interactions" stands out, which is a metric that measures the spatio-temporal dissimilarity of interactions between species. Studies on the interactions between ants and plants point out that the β-diversity of interactions between communities increases with geographic distance and that the rewiring in interactions of shared species between communities is its main component. Ants, however, are involved with several other mutualistic partners, including trophobiont insects. However, despite the relevance, little is known about how this type of mutualistic interaction varies spatially. In this sense, we explore the dissimilarities of mutualistic interactions between ants and trophobiont insects at different spatial scales and along with the geographical distance in communities under similar abiotic and biotic conditions. We also assessed the contribution of the ‘species turnover’ and ‘interactions rewiring’ components of β-diversity of interactions. We found that the β-diversity of ant-trophobiont interactions is greater at the regional scale and increases with the geographical distance between two communities. The ‘species turnover’ component proved to be more important for the β-diversity of interactions. We suggest that the fidelity that results from the dominant behavior of some ant species over the trophobionts that offer more qualified resources leads to a low rewiring of interactions between shared species by two communities. However, many species are not shared between communities, especially with the increasing distance between them. This is due to the presence of sub-dominant species of ants and less aggregating trophobionts, which are usually expelled and present high turnover, generating relatively unique communities in space already on the local scale. Nevertheless, these processes seem to act in a secondary way on a regional scale, potentially driven by historical processes, such as limited dispersion and speciation. We took an important first step towards understanding the role of spatial scales and geographic distance on protection mutualisms. We show that the ant-trophobiont interactions, occurring in similar abiotic and biotic conditions, changed with the geographical distance and the spatial scale, mainly due to the change in species composition.